Evaluation of Quality Services at PT. Hajar Aswad Mubaroq - Dani, Akhmad Anwar; Gemelli, Teha Aulia; Sativa, Alfiana (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
This study aims to determine the quality of services provided byPT. Hajar Aswad Mubaroq to the congregation; to find out theobstacles faced in the implementation of Umrah plus Turkish worship,and to evaluate the services provided by the bureau to thepilgrims. Using qualitative research methods with descriptive analysistechniques. The main data were obtained through interviews withemployees and the study of related documents. It was concluded thatPT. Hajar Aswad Mubaroq has done a good service to thecongregation from departure to return home. So that the results of theevaluation of the services of PT. Hajar Aswad Mubaroq was verysatisfying for the congregation. Obstacles faced when carrying outUmrah and tours in Turkey, sick pilgrims, lost pilgrims and late pilgrimsand elderly pilgrims.